THE USE OF TEACHING PROFICIENCY THROUGH READING AND STORYTELLING (TPRS) METHOD IN TEACHING SPEAKING SKILLS - Nugraha, Muhammad Anjar (2017)
This study was aimed to investigate the effectiveness of Teaching Proficiency through Reading and Storytelling (TPRS) method in teaching speaking skills to the tenth graders in one of senior high schools in Bandung, and their attitudes after the implementation of this method. Findings indicated that the students' speaking score of the experimental group that was treated by using language acquisition-based in TPRS was significantly higher than the control group that was treated by using language learning-based in non-TPRS. TPRS made the students to participate more, to feel not afraid, to avoid anxiety, and to have more confidence in speaking English. ;---Penelitian ini bertujuan untuk mengetahui efektivitas metode pengajaran Teaching Proficiency through Reading and Storytelling (TPRS) dalam mengajar keterampilan berbicara kepada siswa kelas X di salah satu SMA di Bandung dan sikap mereka setelah pelaksanaan metode tersebut dikelas. Hasil analisis data menunjukkan bahwa skor berbicara siswa dari kelompok eksperimen yang diberikan perlakuan dengan menggunakan metode TPRS berbasis pemerolehan bahasa secara signifikan lebih tinggi daripada kelompok kontrol yang diberikan perlakuan non-TPRS berbasis pembelajaran bahasa. Metode TPRS mampu membuat siswa untuk lebih berpartisipasi, merasa tidak takut melakukan kesalahan, menghindari kecemasan, dan lebih percaya diri dalam berbicara bahasa Inggris.